The Association Between STAT4 rs7574865 Polymorphism and the Susceptibility of Autoimmune Thyroid Disease: A Meta-Analysis - Gao, Xueren; Wang, Jianguo; Yu, Yongguo (Frontiers in Genetics, 2019)
Objectives: The signal transducer and activator of transcription 4 (STAT4) gene encodes an important transcription factor that transmits signals induced by several cytokines associated with autoimmune diseases, and has been identified as a susceptibility gene for numerous autoimmune disorders. The association between STAT4 rs7574865 polymorphism and the susceptibility of autoimmune thyroid disease (AITD) has been investigated in previous case-control studies. However, the investigation results were inconsistent. Hence, a meta-analysis was performed to draw a more reliable conclusion about it. Methods: All relevant studies were searched in Embase, PubMed, Web of Science, and China National Knowledge Infrastructure, till August 20, 2018. The pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of the association. Results: A total of five independent case-control studies with 1707 AITD patients and 2316 controls were included in the present meta-analysis. The overall pooled analysis indicated that STAT4 rs7574865 polymorphism was significantly associated with AITD susceptibility [TT vs. GG: OR=1.63, 95%CI=1.24-2.15, PZ=0.0005; TT vs. (TG + GG): OR=1.55, 95%CI=1.26-1.91, PZ<0.0001]. However, the subgroup analysis showed a significant association of STAT4 rs7574865 polymorphism with AITD susceptibility in Asian population, but not in African population. STAT4 rs7574865 polymorphism was significantly associated both with Graves' disease (GD) and Hashimoto's thyroiditis (HT) susceptibility. Conclusion: This meta-analysis showed a significant association between STAT4 rs7574865 polymorphism and AITD susceptibility. However, further studies with larger sample sizes and other ethnicities are still required to confirm the findings.